PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS X SMK BISNIS DAN TEKNOLOGI BEKASI - Maulana Panji; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
This study aims to determine the quality of spiritual intelligence of class Xstudents of SMK Business and Technology Bekasi, to find out how the quality oflearning achievement of Islamic Religious Education students of class X SMK Businessand Technology Bekasi. And to find out the relationship between spiritual intelligenceand learning achievement of Islamic Religious Education class X SMK Business andTechnology Bekasi. This research is a quantitative research using the correlationmethod. The population in this study were students with a sample based on proportionalrandom sampling technique. The formula used is the Slovin formula and obtained anumber of 74 students. The results showed that there was a significant relationshipbetween spiritual intelligence and learning achievement in Islamic education. This isknown through the acquisition of the Pearson correlation results obtained with asignificant value = 0.029 which means a significant value < (0.10) so that H0 is rejectedand H1 is accepted.